2021
DOI: 10.15678/ier.2021.0701.02
|View full text |Cite
|
Sign up to set email alerts
|

Practical knowledge in preparing financial statements and ICT-enabled financial plans: An empirical study among entrepreneurial students in Oman

Abstract: This paper aims to examine practical knowledge in preparing financial statements (FStts), practical knowledge in information and communication technology (ICT) and ICT-enabled financial plan (ICTeFP) among entrepreneurial students within Universities in Oman. Research Design & Methods: Primary data were collected from university students to analyze practical knowledge in preparing FStts and related ICT skills. Items of FStts were considered to measure entrepreneurial students' practical knowledge to prepare FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Finally, it is suggested that CSR spending should make as a compulsory provision to all the listed companies in Oman. In the future, if CSR spending (say, 0.5% on profit after tax) made compulsory, as per generally accepted accounting principles (GAAP) can enable firms or companies to determine automatically by information communication technology (ICT) enabled accounting, auditing and compliance (Thottoli, 2020a, b, 2021d; Thottoli et al ., 2019a, b, c; Thottoli and Thomas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is suggested that CSR spending should make as a compulsory provision to all the listed companies in Oman. In the future, if CSR spending (say, 0.5% on profit after tax) made compulsory, as per generally accepted accounting principles (GAAP) can enable firms or companies to determine automatically by information communication technology (ICT) enabled accounting, auditing and compliance (Thottoli, 2020a, b, 2021d; Thottoli et al ., 2019a, b, c; Thottoli and Thomas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cloud computing-based technology enforces certain threats, such as, for instance, inadequate protection in terms of data security and confidentiality (Chou, 2015). Internet hackers are endangering organizations, individuals and other organizations by stealing data or by triggering business operational disruption that can have a significant effect on the reliability of source data entered in the financial statements (Barta, 2018;Thottoli, 2021c). The adoption of technology includes elements such as environmental factors, the non-availability of technically experienced auditors in the job market, the size of a client's business, expectations and the unavailability of GAS in a variety of languages (Widuri et al, 2016).…”
Section: Technological Challengesmentioning
confidence: 99%
“…With an emphasis on evolving the flea market, the digital revolution in financial services introduces business opportunities to transform its business model for social and economic development for a better customer experience (Abdulquadri et al, 2021). This research problem is exacerbated by the fact that information communication technology (ICT) and research on digital transformation have traditionally been conducted in academic silos (Thottoli, 2021a(Thottoli, , 2021b(Thottoli, , 2022. Thus, theoretically significant insights on what are the emerging topics in the field of digital transformation in financial services are currently unavailable.…”
Section: Introductionmentioning
confidence: 99%